Muscle RAS oncogene homolog (MRAS) recurrent mutation in Borrmann type IV gastric cancer. (28th November 2016) - Yasumoto, Makiko; Sakamoto, Etsuko; Ogasawara, Sachiko; Isobe, Taro; Kizaki, Junya; Sumi, Akiko; Kusano, Hironori; Akiba, Jun; Torimura, Takuji; Akagi, Yoshito; Itadani, Hiraku; Kobayashi, Tsutomu; et al.
Abstract: The prognosis of patients with Borrmann type IV gastric cancer (Type IV) is extremely poor. Thus, there is an urgent need to elucidate the molecular mechanisms underlying the oncogenesis of Type IV and to identify new therapeutic targets. Although previous studies using whole‐exome and whole‐genome sequencing have elucidated genomic alterations in gastric cancer, none has focused on comprehensive genetic analysis of Type IV. To discover cancer‐relevant genes in Type IV, we performed whole‐exome sequencing and genome‐wide copy number analysis on 13 patients with Type IV. Exome sequencing identified 178 somatic mutations in protein‐coding sequences or at splice sites. Among the mutations, we found a mutation in muscle RAS oncogene homolog ( MRAS ), which is predicted to cause molecular dysfunction. MRAS belongs to the Ras subgroup of small G proteins, which includes the prototypic RAS oncogenes. We analyzed an additional 46 Type IV samples to investigate the frequency of MRAS mutation. There were eight nonsynonymous mutations (mutation frequency, 17%), showing that MRAS is recurrently mutated in Type IV. Copy number analysis identified six focal amplifications and one homozygous deletion, including insulin‐like growth factor 1 receptor ( IGF1R ) amplification. The samples with IGF1R amplification had remarkably higher IGF1R mRNA and protein expression levels compared with the other samples. This is the first report of MRAS recurrent mutation in human tumor samples. Our results suggest that MRAS mutation and IGF1R amplification could drive tumorigenesis of Type IV and could be new therapeutic targets. Abstract : This is the first report of the genomic profile of Borrmann type IV gastric cancer. We found that muscle RAS oncogene homolog ( MRAS ) is recurrently mutated in Borrmann type IV gastric cancer. We also detected IGF1R gene amplification and that it was correlated with high levels of mRNA and protein expression.